Butterfly fauna (insecta: Lepidoptera: Papilionoidea) and larval host plant in Bongaon town, West Bengal, India - Biswas, Sourabh; Mukhopadhyay, Shiladitya; Dey, Rajib (Academia Journal of Biology, 2022)
An appraisal of butterfly species diversity was carried out in the suburban town of Bongaon, southern West Bengal, India whose butterfly faunal diversity remained undocumented. A total of 76 species of butterflies were recorded from October 2018 to October 2019. The highest number of butterflies were recorded belonging to the family Nymphalidae (27 species), followed by Lycaenidae (21 species), Hesperiidae (13 species), Pieridae (8 species) and Papilionidae (7 species). Among the 76 butterfly species that have been recorded, nine species come under the protection category as per the Indian Wildlife (Protection) Act, 1972. Over the study period, 54 species of larval host plants were also documented. This communication will be the first comprehensive work on butterflies of Bongaon town and serve as baseline data for future research on the butterfly.